Characterization of an alkaline protease with high quality bating potential in leather processing from Bacillus licheniformis MZK05M9 mutant - Mamun, Md. Arafat Al; Khan, Md. Murad; Akand, Md. Nahinur Rahmam; Khan, Shakila Nargis; Hoq, Md. Mozammel (International Journal of Biological Research, 2015)
An alkaline protease from Bacillus licheniformis MZK05M9 (BlM9), a mutant strain developed in our laboratory, has been partially purified and characterized for its robustness and eco-friendly application potential in processing of hides and skins for leather manufacturing and detergent industries. The enzyme was purified 2.70 fold with specific activity of 1624U/mg in comparison to crude enzyme extract by using ammonium sulfate precipitation, dialysis and Sephadex G-75 column chromatography. The molecular mass of the enzyme was 27.2 kDa as judged by SDSâ€“PAGE. The purified protease had a pH optimum of 8.5 and temperature optimum of 55Â°C. According to the inhibition profiles obtained with the various protease inhibitors, it was confirmed that the partially purified protease belongs to the serine protease type. The activity of partially purified enzyme was enhanced by calcium, magnesium, barium, potassium and manganese ions and strongly inhibited by mercury ion. In addition, the protease showed remarkable stability in the presence of 1% SDS; 1, 3 and 5% Triton X-100 and H2O2, which comprise the common bleach-based detergent formulation. The enzyme was found equally efficient to a commercial enzyme Oropon K (one of the commercial enzymes imported into Bangladesh for bating purpose) in bating of animal hide as proved by different comparative qualitative tests such as tensile strength, percent of elongation, stitch tears strength, water vapor permeability, grain crack strength and tongue tearÂ strength tests. In addition, the stability profile (pH, temperature and surfactants) and blood stain removal data also revealed its suitability for application in detergent industry.